Oil sands production scheduling and waste management with optimum cut-off grade policy. (2018) - Hosseini, Navid Seyed; Ben-Awuah, Eugene
Cut-off grade is the criterion that separates ore from waste and it determines the amount of ore and waste material in the final pit limit. To generate an optimum production schedule for the mine life, cut-off grade optimisation is used to determine the cut-off grade, duration of mining of the grade and the amount of material mined. This research developed a heuristic optimisation model that generates an optimum cut-off grade policy and a schedule for ore and waste material including overburden (OB), interburden (IB) and tailings coarse sand (TCS) dyke materials for dyke construction in oil sands mining. Scenarios investigated include: no stockpiling and stockpiling with limited reclamation duration. The scenario of reclaiming the stockpile after one year had the highest net present value (NPV) as well as the highest cut-off grade profile. Reclaiming the stockpile after two years had less NPV due to reduction in processing recovery resulting from oxidation.